Disenchantment or Conflict? Egil Asprem and ‘Science and Religion’ Discourses - Drees, Willem B. (Journal of religion in Europe, 2015)
In his The Problem of Disenchantment, Egil Asprem offers an interesting view of discourses on science and religion. Despite the dominance of ‘conflicts’ in public perception, the ‘independence’ approach might be more deeply rooted in modern culture. Asprem studies ‘scientific’ movements that oppose disenchantment. In this paper i raise the question of why quantum physics was successful, whereas other revisions of ‘science’ were not. Of the natural theologies discussed, this paper offers some comments on ‘emergence’ and on ‘quantum mysticism’. Asprem presents himself as a methodological naturalist; a position that is in principle open to the study of parapsychology and other ‘spiritual’ claims. He considers theism to be incompatible with such a methodological naturalism, whereas I suggest that an epistemically agnostic theism is also appropriate, combining methodological naturalism and disenchantment.